Liquidity and Rentability to Share Price - Naninsih, Nur; Umar, Rahmawati; Tarawiru, Yasri; Misrah, Misrah; Bintari, Wisang Candra (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study aims to determine the effect of liquidity and profitability on stock prices simultaneously and partially in food and beverage companies listed on the Indonesia Stock Exchange (IDX). In this study, liquidity is measured by the quick ratio, and rentabili-tas is measured by return on equity. This research is quantitative. The population in this study were all food and beverage industry companies listed on the Indonesia Stock Exchange, as many as 18 companies. The sampling technique used is purposive sampling, where, based on predetermined criteria, a sample of 10 companies is obtained. The data source of this research is secondary data, namely data obtained from the company's financial statements. The data analysis methods used in this research are descriptive statistical analysis, partial test, simultaneous test, and determination coefficient test. The results showed that the liquidity and profitability variables partially had a positive and insignificant effect on the share price of food and beverage companies listed on the Indonesia Stock Exchange (IDX). Simultaneously, liquidity and profitability variables affect stock prices.